Temperature and Stress Dependence of Screw Dislocation Mobility in Nb-V-Ta Alloys Using Kinetic Monte Carlo Simulations - Zhou, Xinran; Marian, Jaime (Frontiers in Materials, 2021)
In this work we present simulations of thermally-activated screw dislocation motion in Nb-Ta-V alloys for two distinct scenarios, one where kink propagation is solely driven by chemical energy changes, i.e., thermodynamic energy differences, and another one where a migration barrier of 1.0 eV is added to such changes. The simulations have been performed using a kinetic Monte Carlo model for screw dislocation kinetics modified for complex lattice-level chemical environments. At low stresses, we find that dislocation motion in the case with no barrier is controlled by long waiting times due to slow nucleation rates and extremely fast kink propagation. Conversely, at high stress, the distribution of sampled time steps for both kink-pair nucleation and kink propagation events are comparable, resulting in continuous motion and faster velocities. In the case of the 1.0-eV kink propagation energy barrier, at low stresses kink motion becomes the rate-limiting step, leading to slow dynamics and large kink lateral pileups, while at high stresses both kink pair nucleation and kink propagation coexist on similar time scales. In the end, dislocation velocities differ by more than four orders of magnitude between both scenarios, emphasizing the need to have accurate calculations of kink energy barriers in the complex chemical environments inherent to these alloys.